The Challenges Facing the Fundamentals of Land Tenure Developments After the Islamic Revolution - bigard tiemouri; shahram mohammadi (آموزه‌‌های فقه مدني)
Social phenomena have arisen with the development of previous phenomena. The legal system and political force are none alone accountable for all social realities and the foundations of the law are formed in the main roots of society and law cannot be analyzed separately from society. The issue of the land tenure is the phenomena that occurred in Iran after the Islamic revolution in the field of legislation which is a kind of rush to provide a solution and respond to the expectations of the revolutionary people by relying on jurisprudential and revolutionary views. The last result of the reasonable men to experiences and by jurisprudence for the benefit of some people in society was the new legislation. The challenges facing the fundamentals of the developments of land tenure have been the reason of discussion in many issues and the records of the subject should be reviewed and adapted in order to analyze it by jurisprudential and legal system. These challenges by identifying the foundations of the developments of land tenure are analyzed in this regard and the goal is not merely to discover jurisprudential rules as the basis. This article analyzes the hypothesis of the absolute impact of revolutionary views on expropriation [dispossession] of private ownership and iqta (Arabic: الإقطاع, Romanized: iqṭāʿ, sectorization) of public property. The result obtained in the end is that it shows the influence of revolutionary views along with social, economic and political conditions on the developments of land tenure after the Islamic revolution.